Comparison of the Therapeutic Effects of Rivaroxaban Versus Warfarin in Antiphospholipid Syndrome: A Systematic Review - Mandana KHODASHAHI; Zahra REZAIEYAZDI; Maryam SAHEBARI (Archives of Rheumatology, 2020)
Objectives: This study aims to review the studies evaluating the therapeutic effects of rivaroxaban versus those of warfarin in patients with antiphospholipid syndrome (APS). Materials and methods: The study included randomized clinical trials, comparative studies, cross-sectional investigations, and case series that focused on the effects of warfarin and rivaroxaban and compared the effects of these anticoagulants in patients with APS. The relevant articles published until 2018 were searched in several databases, including PubMed, Scopus, ScienceDirect, Google Scholar, Embase, and Web of Science. Results: The findings of the reviewed studies showed that rivaroxaban can be used as an effective and safe alternative to warfarin in APS patients. However, the effectiveness of rivaroxaban in the prevention of thrombosis in high-risk APS patients is suspected. Conclusion: Given the high risk of using rivaroxaban in thrombotic APS patients with labile international normalized ratio (INR) or poor adherence to INR monitoring, it is not suggested to use this agent for these patients.